2017
DOI: 10.1051/mbcb/2016057
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for intraosseous mandibular haemangioma. Case report and literature review

Abstract: -Introduction:Intraosseous mandibular haemangiomas are rare benign tumors.To this date there is no general consensus regarding their treatment. Observation: The authors present a case of a 56-year-old patient with swelling of the basilar left edge, without any other associated symptom. Radiolucent images with a well-defined honeycomb structure supports the vascular injury found using dental orthopantomography and cone beam computed tomography. Dynamic magnetic resonance angiography (MRA) showed mild intense in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Robson and many other studies showed female to be more predilicted than men with a ratio of almost 2. [ 11 12 13 14 15 ] But in this case, the patient was a 47-year-old male which was not in accordance with the study conducted by Smith et al . and Zlotorgoski and did not coincide with the studies mentioned in the literature.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Robson and many other studies showed female to be more predilicted than men with a ratio of almost 2. [ 11 12 13 14 15 ] But in this case, the patient was a 47-year-old male which was not in accordance with the study conducted by Smith et al . and Zlotorgoski and did not coincide with the studies mentioned in the literature.…”
Section: Discussioncontrasting
confidence: 61%
“…When detected in mandible, the body of the mandible is the most common site to be affected. [ 15 17 ] Anna et al . and Moore et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation